N4-phenylquinazoline-4, 6-diamine as a tunable fluorescent scaffold for the development of fluorescent probes. (February 2023) - Lee, Jaeseok; Choi, Sang-Kee; Aslam, Adil S.; Lim, Woojeong; Lee, Juyong; Ko, Junsu; Ryu, Chan Hee; Lee, Kang Mun; Jung, Young Mee; Yoo, Hyuk Sang; Park, Ju Hyun; Lee, Sanghee; et al.
Abstract: Fluorescent molecules have been used for various applications in biological system monitoring. Considering the complexity of cellular systems, there is a huge demand for diverse fluorescent organic molecular scaffolds. However, only a limited number of fluorescent scaffolds have been reported due to the lack of a rational design strategy. We serendipitously discovered N4-phenylquinazoline-4, 6-diamine as a fluorescent scaffold with turn-on characteristics. To improve the photophysical property of the initial fluorescence molecule, we synthesized derivatives of the N4-phenylquinazoline-4, 6-diamine and found systematic correlation between electronic density of the phenyl substituent of the scaffold and fluorescence intensity. Through tuning the photophysical property of the scaffold and a rational design strategy, we developed N4-dichlorophenylquinazoline-4, 6-diamine as a potential fluorophore for various biological applications. To prove the value of the developed fluorescent scaffold, we devised formaldehyde (FA) fluorescent sensor by tailoring amine on 6-position of N4-dichlorophenylquinazoline-4, 6-diamine to employ a 2-aza-Cope rearrangement as the molecular detection mechanism with double-digit nanomolar detection limits. FA level in live HeLa cells were successfully visualized with the probe, exhibiting that N4-dichlorophenylquinazoline-4, 6-diamine can serve as a useful molecular scaffold for offering various fluorescent sensors toward the investigation of physiological and pathological processes in live cells. Graphical abstract: Image 1 Highlights: A new tunable fluorescent molecular scaffold, N4-phenylquinazoline, was discovered. A structure photophysical property relationship of the scaffold was unveiled. The relationship has led to the rational design of a formaldehyde sensor, QFP. Reaction between formaldehyde and QFP trigger aza-Cope rearrangement. Rearrangement reaction of QFP allowed sensing of formaldehyde in live cell.